How do you solve 8-4(m + 5) = 3(m-9)?

2 Answers
Mar 29, 2018

m = 2.14

Explanation:

Begin by using the distributive property to simplify. Here is a helpful image if you need a refresher on the distributive property:
https://sites.google.com/a/d83.org/math-6/chapter-6/6-6-the-distributive-propertyhttps://sites.google.com/a/d83.org/math-6/chapter-6/6-6-the-distributive-property

8 - 4(m + 5) = 3(m - 9)

8 - 4m - 20 = 3m - 27

Now add like terms and solve:
8 - 4m - 20 = 3m - 27

-12 - 4m = 3m - 27

-4m = 3m - 15

-7m = - 15

-m = -2.14

Multiply both sides by -1 to change it to a positive answer:
m = 2.14

Mar 29, 2018

15/7

Explanation:

8-4m-20=3m-27

-4m-12=3m-27

-4m-3m=-27+12

-7m=-15

m=15/7